The effects of Acanthus ilicifolius chloroform extract on TLR-2 expression of macrophages in oral candidiasis - Dwi Andriani; Agni Febrina Pargaputri (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Immunosuppressed conditions due to long-term corticosteroid and tetracycline consumption are susceptible to fungal invasion, especially by Candida albicans (C. albicans), that requires treatment of oral candidiasis. Toll like receptor-2 (TLR-2) plays a role in candida recognition. Nystatin is regularly employed for oral candidiasis, but produces certain side-effects. Chloroform extract of Acanthus ilicifolius (A. ilicifolius) leaves represents both a potent inhibitor of C. albicans growth and an antioxidant. Purpose: This study aimed to compare the effect of A. ilicifolius leaf chloroform extract and nystatin treatment on TLR-2 expression in oral candidiasis immunosupressed models. Methods: This study constitutes a true experimental investigation incorporating a post test-only control group design. 20 healthy male Rattus novergicus (Wistar), aged 12 weeks and with an average weight of 250g, were immunosuppressed through oral administration of dexamethasoneand tetracycline for a period of 21 days before being induced with C. albicans (ATCC-10231) 6 x 108 for two weeks. The subjects were divided into five groups (n=4/group): healthy (H), no-treatment(P), nystatin treatment(N), A. Ilicifollius (8%) treatment (AI-1) and A. ilicifollius (16%) treatment (AI-2). The subjects were treated for 14 days, with their tongue being subsequently biopsied. TLR-2 expression was subjected to immunohistochemical examination, observed under a microscope (400x magnification) and statistically analyzed (one-way Anova, LSD-test, p<0.05). Results: TLR-2 expression of P (6.25 ± 2.5), N (11.25 ± 0.96), AI-1 (13.00 ± 1.15), AI-2 (12.75 ± 1.7) was higher than H (1.75 ± 0.5). Significant differences existed between N to P, N, AI-1, AI-2; P to N, AI-1 and AI-2 (p<0.05). No significant differences were present between N, AI-1 and AI-2 (p < 0.05). Conclusion: A. ilicifolius extract can increase expression of TLR-2 in oral Candidiasis-immunosuppressed models. A. ilicifolius extract produces the same effect in increasing TLR-2 expression when compared to nystatin.